EXPLORING INTEGRATION OF TECHNOLOGY IN ASSESSING MATHEMATICS LEARNING IN EARLY GRADES: A BIBLIOMETRIC PERSPECTIVE ON RESEARCH PATTERNS, GAPS, AND TRENDS - Sungwa, Reuben (International Online Journal of Education and Teaching, 2025)
The integration of technology in early childhood education has the potential to transform learning, particularly in early mathematics. However research on its use in assessment remains fragmented, with significant disparities between high-income and low-income regions. This study addresses the gap by analyzing trends, gaps, and patterns in technology-enhanced assessment in early childhood mathematics education. Utilizing a bibliometric approach, data from the Dimensions database (2010–2023) were analyzed using publication trends, citation metrics, and network mapping tools. The findings reveal a significant rise in research post-2020, dominated by contributions from high-income countries such as the United States and Russia, while resource-constrained regions remain underrepresented. Leading authors, including Daphina Bassok and Anna Rorem, and key institutions like the University of Virginia have significantly shaped the field. Influential journals such as Sustainability and Computers and Education highlight interdisciplinary approaches to bridging the digital divide. Despite progress, notable research gaps persist in addressing equitable access and implementation challenges in low-resource settings. This study provides valuable insights to guide future research, policy, and practical interventions aimed at fostering inclusive, technology-driven assessments that enhance mathematics learning for young learners worldwide.